A new method to quantify the human visual threshold from melanopsin sensitive ganglion cells - Rabin, Jeff; Poole, Erica; Price, William; Kaur, Gurjiv; Hall, Kiana; Sailors, Venessa; Andrews, Brazil; Somphruek, Rathanart (Frontiers in Cellular Neuroscience, 2023)
Traditional photoreceptors utilize the chromophore retinal to absorb light coupled with a unique opsin protein to specify receptor spectral sensitivity. Light absorption triggers a cascade of events transducing light energy to neural signals beginning with graded potentials in receptors (rods and cones) and bipolar cells in outer and middle retina eventuating in action potentials at the inner retinal amacrine and ganglion cell levels. Unlike traditional photoreceptors, ganglion cells in the inner retina (intrinsically photosensitive retinal ganglion cells, ipRGCs) absorb short wavelength, blue light utilizing their photopigment melanopsin. Assessment across multiple species show that the ipRGCs mediate myriad visual and non-visual functions including photo-entrainment and circadian rhythms, the pupillary light reflex, sleep, alertness, cognition, mood, and even conscious visual perception. Some ipRGC functions can persist despite blindness in animal models and humans exemplifying their multidisciplinary control of visual and non-visual functions. In previous research we used selective chromatic adaptation (blue stimulus on a bright amber field) to suppress input from rods, red and green sensitive cones to identify retinal and cortical responses from ipRGCs. Herein we used a similar approach, coupled with a filter to block input from blue sensitive cones, to develop a clinically expedient method to measure the full-field, putative visual threshold from human ipRGCs. This metric may expand our ability to detect, diagnose and monitor ocular and neurologic disease and provide a global retinal metric of ipRGCs as a potential outcome measure for studies using gene therapy to arrest and/or improve vision in hereditary retinal diseases.